In hot water? Assessing the link between fundamental thermal physiology and predation of juvenile Chinook salmon. Issue 11 (13th November 2022) - McInturf, Alexandra G.; Zillig, Ken W.; Cook, Katherine; Fukumoto, Jacqueline; Jones, Anna; Patterson, Emily; Cocherell, Dennis E.; Michel, Cyril J.; Caillaud, Damien; Fangue, Nann A.
Abstract: In light of ongoing environmental change, understanding the complex impact of interacting stressors on species, communities, and ecosystems is an important challenge. Many studies to date examine the effects of potential stressors on a single species of concern. Yet these effects often resonate throughout a community and may produce changes in ecosystem dynamics that are equally critical to species resilience. The aim of this study was to develop a mechanistic understanding of how a rapidly changing stressor, water temperature, will alter trophic interactions among ectothermic fish species. In our region, California's Sacramento–San Joaquin River Delta system, it has been speculated that the decreased survivorship of juvenile Chinook salmon ( Oncorhynchus tshawytscha ) in warming waters may be caused partly by increased predation. Temperature influences metabolic rate functions and the amount of energy available for fitness‐relevant parameters (i.e., swim performance and escape response). Consequently, we hypothesized that these patterns of predation emerge due to a physiological advantage of predators over prey at warmer temperatures. To explore this, our first objective was to determine the fundamental thermal physiology of juvenile Chinook salmon and their potential predators in the Delta. Three physiological performance traits were measured for each species across a spectrum of temperatures: aerobic scope, burst speed, and the ability to burst repeatedly. For our second objective, we assessed whether the effect of temperature on these performance traits predicted the outcome of predation trials conducted across the same temperature spectrum. We found that temperature effects were species or population specific. Additionally, absolute burst swimming ability and the relative burst performance between predator and prey were stronger indicators of trophic dynamics than aerobic scope. Our analyses also confirmed that a major predator in the Delta, specifically largemouth bass ( Micropterus salmoides ), is more thermally adapted to higher temperatures and will likely consume salmon with an increasing frequency as waters warm. Thus, we show that an improved understanding of how fundamental thermal physiology impacts predation can provide ecosystem managers with better tools to predictively model predation upon juvenile salmon based on prevailing and future water temperatures.